Medial septum: relevance for social memory - Griguoli, Marilena; Pimpinella, Domenico (Frontiers in Neural Circuits, 2022)
Animal species are named social when they develop the capability of complex behaviors based on interactions with conspecifics that include communication, aggression, mating and parental behavior, crucial for well-being and survival. The underpinning of such complex behaviors is social memory, namely the capacity to discriminate between familiar and novel individuals. The Medial Septum (MS), a region localized in the basal forebrain, is part of the brain network involved in social memory formation. MS receives several cortical and subcortical synaptic and neuromodulatory inputs that make it an important hub in processing social information relevant for social memory. Particular attention is paid to synaptic inputs that control both the MS and the CA2 region of the hippocampus, one of the major MS output, that has been causally linked to social memory. In this review article, we will provide an overview of local and long range connectivity that allows MS to integrate and process social information. Furthermore, we will summarize previous strategies used to determine how MS controls social memory in different animal species. Finally, we will discuss the impact of an altered MS signalling on social memory in animal models and patients affected by neurodevelopmental and neurodegenerative disorders, including autism and Alzheimer’s Disease.